Anesthetic Efficiency of Three Medicinal Plant Oils for Aquatic Species: Coriander Coriandrum sativum, Linaloe Tree Bursera delpechiana, and Lavender Lavandula hybrida. Issue 3 (12th September 2019) - Can, Erkan; Kızak, Volkan; Can, Şafak Seyhaneyıldız; Özçiçek, Esin
Abstract: This study evaluated the potential of three essential oils (EOs) that were obtained from coriander Coriandrum sativum (CEO), linaloe tree Bursera delpechiana (BEO), and lavender Lavandula hybrida (LEO) as anesthetic agents. Convict Cichlids Amatitlania nigrofasciata (Günther 1867) were exposed to eight concentrations of anesthetic (50, 75, 100, 125, 150, 200, 250, and 300 μL/L). After exposure to the anesthetic, the fish were transferred to clean water to recover. All of the EOs produced an anesthetic effect after exposure to the compounds for 30 min at the minimal effective concentration (MEC), which was identified according to deep anesthesia (A5 < 3 min) and full recovery (R3 < 5 min) times. At 50 and 75 μL/L, the total loss of equilibrium was not observed for all tested EOs. The total loss of reflex was induced at a faster rate with higher concentrations of anesthetic in all groups. The recovery time generally increased as the concentration of the anesthetic increased. These findings suggest that CEO, BEO, and LEO are all novel potential anesthetics for aquaculture, and the optimal concentrations were identified as 150 μL/L (A5 ; 156 ± 1.7 s and R3 ; 165 ± 2.9 s), 125 μL/L (A5 ; 176 ± 3.5 s; R3 ; 125 ± 2.0 s), and 200 μL/L (A5 ; 20.1 ± 2.4 s and R3 ; 162 ± 3.4 s), respectively. When considering the active ingredients of EOs, this study also demonstrated that future studies should be focused on the major components such as linalyl acetate, 1.8‐cineole, α‐pinene, geraniol, and linalool. Their synergistic effects should be examined in herbal anesthetic treatments, since new commercial anesthetics will likely contain them.